2007
DOI: 10.1890/05-1460.1
|View full text |Cite
|
Sign up to set email alerts
|

Nload: An Interactive, Web‐based Modeling Tool for Nitrogen Management in Estuaries

Abstract: Abstract. Eutrophication of estuaries is an increasing global concern that requires development of new tools to identify causes, quantify conditions, and propose management options that address this environmental problem. Since eutrophication is often associated with increased inputs of land-derived nitrogen to estuaries, we developed NLOAD, a user-friendly, web-based tool that brings together six different published models that predict nitrogen loading to estuaries and two models that estimate nitrogen concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…While our result for the Trout River estuary (380 kg NO 3 ‐N/ha estuary/year) is comparable to an intermediate loading, it is evident that the McIntyre Creek load of 1700 kg NO 3 ‐N/ha estuary/year significantly exceeds values for Waquoit Bay sub‐estuaries or other estuaries in the Cape Cod, MA, USA, area (Carmichael et al , 2004). Indeed the annual loading to McIntyre Creek estuary appears to be one of the highest values reported in the literature (Table IV in Bowen et al , 2007b). Although many factors other than N loading may affect estuarine functioning (e.g.…”
Section: Discussionmentioning
confidence: 80%
“…While our result for the Trout River estuary (380 kg NO 3 ‐N/ha estuary/year) is comparable to an intermediate loading, it is evident that the McIntyre Creek load of 1700 kg NO 3 ‐N/ha estuary/year significantly exceeds values for Waquoit Bay sub‐estuaries or other estuaries in the Cape Cod, MA, USA, area (Carmichael et al , 2004). Indeed the annual loading to McIntyre Creek estuary appears to be one of the highest values reported in the literature (Table IV in Bowen et al , 2007b). Although many factors other than N loading may affect estuarine functioning (e.g.…”
Section: Discussionmentioning
confidence: 80%
“…This increase from surface water runoff over~10 years suggests that continued development and land alteration of the BB-LEH watershed likely play significant roles in nitrogen enrichment of this estuary. These TN load estimates were based on a measure of both DIN (NH 4 þ þ NO À 3 þ NO À 2 ) and dissolved organic nitrogen (DON) species in major river basins and represent the TN load delivered from the watershed to the receiving estuarine waters estimated by applying the NLOAD model described by Bowen et al (2007). The ratios between TN and TP loads are thus not representative of the nutrient ratios in the water column.…”
Section: Nutrientsmentioning
confidence: 99%
“…These previous nutrient/water temperature model inter-comparison studies have shown the importance of evaluating the performance of water quality models and highlighted the need of common input data to provide consistent water quality model output for comparison [41,43,45].…”
Section: Previous Water Quality Mipsmentioning
confidence: 99%